The Effect of Human Resources Abilities on entrepreneurial orientation: An Exploratory Study of the Opinions of a Sample of Employees at Tikrit University - Arshed Essa Khudhur (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The study aimed, to identify the relationship and impact, of human resources capabilities represented by (capacity building, activity credibility, and technology champion) on the entrepreneurial orientation of the organization and by applying it to Tikrit University, by shedding light on the human resources capabilities at Tikrit University and explaining its effective role in the entrepreneurial orientation. A questionnaire for this purpose was distributed to a random sample of directors and employees of the human resources divisions in the colleges, centers and administrative units affiliated with the University of Tikrit, numbering (113) people. To verify the research hypotheses, statistical methods were used represented by correlation analysis and multiple linear regression analysis, and using the statistical program SPSS-26. The data was analyzed and the results were drawn, the most important of which is that the perceptions and impressions of respondents in the research sample about the areas of human resources capabilities and entrepreneurial orientation were positive and to a high degree. There is a significant, correlation between the areas of human resources capabilities and the field of entrepreneurial orientation. The greater the importance of human resources capabilities among employees at Tikrit University, the greater the importance of the role. The university's entrepreneurial orientation to a greater extent. It was also shown that there is a significant impact of human resources capabilities on the entrepreneurial orientation of Tikrit University, as these capabilities contribute to explaining (74%) of the variance in the entrepreneurial orientation. Capacity building is considered the most influential area in the entrepreneurial orientation, followed by the field of credibility of activity. Then the field of technology champion , and one of the most prominent recommendations is to pay attention to human capital with experience and high efficiency and give them their role in directing workers and benefiting from their experience in order to reach leadership.